Ca(2+) Regulation of TRP Ion Channels - Hasan, Raquibul (Int J Mol Sci, 2018)
Ca(2+) signaling influences nearly every aspect of cellular life. Transient receptor potential (TRP) ion channels have emerged as cellular sensors for thermal, chemical and mechanical stimuli and are major contributors to Ca(2+) signaling, playing an important role in diverse physiological and pathological processes. Notably, TRP ion channels are also one of the major downstream targets of Ca(2+) signaling initiated either from TRP channels themselves or from various other sources, such as G-protein coupled receptors, giving rise to feedback regulation. TRP channels therefore function like integrators of Ca(2+) signaling. A growing body of research has demonstrated different modes of Ca(2+)-dependent regulation of TRP ion channels and the underlying mechanisms. However, the precise actions of Ca(2+) in the modulation of TRP ion channels remain elusive. Advances in Ca(2+) regulation of TRP channels are critical to our understanding of the diversified functions of TRP channels and complex Ca(2+) signaling.